The Provincial Press & the Outbreak of War. A Unionist View in Worcestershire. (September 2014) - Beeching, Nick
<x content-type="archive" xml:space="preserve">Abstract</x> This article tests three contentions advanced by Adrian Gregory in his book The Last Great War: first, that the reaction to the outbreak of war in 1914 was not one of universal unthinking enthusiasm; second, that the provincial press took a sober and critical view of the imminent outbreak of hostilities; and third, that volunteering was a more layered experience than a simple rush to the colours. The methodology adopted has been to review the Berrow's Journal newspaper between January 1914 and January 1915, looking particularly at the editorial views of the paper, views expressed through the paper via 'Letters to the Editor', accounts of meetings and quotations from speakers and the events and information that the newspaper chose to report. Berrow's Journal has been chosen as a weekly newspaper and as a Unionist newspaper in a strongly Unionist region, where if jingoism were to be found, a superficial reading might suggest it would be found there. The figures on enlistments quoted in the newspaper will be tested against the author's own research using fatal casualties as a representative sample.